Food and recipes of the Revolutionary War - Erdosh, George, 1935- (New York : PowerKids Press, 1997)
Describes the kinds of foods commonly consumed by colonists, including soldiers, during the time of the American Revolutionary War. Includes recipes.
Freedom at last -- Food of the time -- Breakfast -- Recipe : frumenty -- A snack after school -- Good food, bad health -- Recipe : revolutionary boiled salad -- Sweet things -- Soldier food -- Army cooking -- Recipe : Minuteman's beef stew -- Enough food during the war -- Recipe : Boston baked beans -- Food after the war.
Includes index.
4.4
3-6
Keywords: Cookery, American -- History -- Juvenile literature; Cookery, American -- History; American cooking -- History; United States -- History -- Revolution, 1775-1783 -- Juvenile literature; United States -- History -- Revolution, 1775-1783.; United States -- History -- 1775-1783, Revolution